Strange Sally Diamond / A Novel - Nugent, Liz (New York : Scout Press, 2023)
Garnering media attention when she tries to incinerate her dead father, reclusive Sally Diamond, beginning to discover the horrors of her early childhood, steps into the world for the first time and soon finds her trust issues severely challenged by a sinister voice from her past she does not remember.
Keywords: Recluses -- Fiction; Fathers and daughters -- Fiction; Fathers -- Death -- Fiction; Mental illness -- Fiction; Misogyny -- Fiction; Ireland -- Fiction; Psychological fiction; Thrillers (Fiction)